Potential of Sri Lankan black tea (Camellia sinensis L.) in dissolution of human kidney stones in vitro - Abeywickrama, K.R.W (My University, 2012)
Previous studies have disclosed that black tea contains between 1.5 - 6.5 mg of soluble oxalates/g tea and thus regular consumption of black tea will lead to a moderate intake of soluble oxalate each day (Savage et al., 2003). Therefore, consumption of black tea may increase the urinary oxalate concentration, possibly leading to an increased risk of kidney oxalate stone formation (Brinkley et al., 1990). On the contrary, it is claimed that its consumption reduces the risk of kidney stones formation and in fact leads to a reduced risk of kidney stone formation by 14% in males (Curhan et al., 1996) and 8% in females (Curhan et al., 1998). Human kidney stones are predominantly made of calcium oxalate (more than 75%) (Savage et al., 2003). Three main mechanisms have been suggested for dissolving oxalate based kidney stones (Savage et al., 2003): an increased urinary flushing leading to high oxalate excretion; an increased level of calcium consumption via food and beverages leading to reduced oxalate absorption in the digestive tract; and by dissolving of calcium oxalate present in the kidney stones by chemical constituents ingested in to the body. The aim of this study was to examine the ability of black tea infusion (BTI) to dissolve kidney stones, since BTI has been shown to reduce urinary oxalate levels (Savage et al., 2003). The study was conducted in vitro on human kidney stones collected following surgery using low grown BOPF grade Sri Lankan orthodox black tea infusion.